Contrastive Analysis of Concord in Arabic, English, and Indonesian - Supardi, Supardi; Jabal, Abdel Karim Muhammad Hassan (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Recognizing the differences in concord among languages will be very important to avoid mistakes in using these languages because concord errors are the most common errors in language use. This article was a contrastive study of concord in Arabic, English, and Indonesian, and the implication of teaching the languages. Through contrastive analysis, the grammatical concord system of the languages was compared to determine the similarities, differences, and teaching implications. Library research was used through a qualitative method. The data was taken mainly from Arabic, English, and Indonesian grammar books. The results showed that the concord in Arabic and English was grammatical, while in Indonesian, it was notional. The element of concord in Arabic was more complex, comprising phrases and clauses, and consisting of five features: person, number, gender, definiteness, and case markers. Meanwhile, the English concord occured on the clause domain of person and number, differing from that of Indonesian which was based on meaning. This study provided an incentive to foreign language tutors, especially,  Arabic and English tutors, to develop strategies in helping students master concord and avoid grammatical errors.